Geographically distributed requirements elicitation - Vat, Nicholas (Rhodes University, Faculty of Commerce, Department of Information Systems, 2000)
The technology revolution has transformed the way in which many organisations do their business. The resultant information systems have increased the decision making powers of executives, leading to increased effectiveness and ultimately to improved product delivery. The process of information systems development is, however, complex. Furthermore, it has a poor track record in terms of on-time and within-budget delivery, but more significantly in terms of low user acceptance frequently attributable to poor user requirements specification. Consequently, much attention has been given to the process of requirements elicitation, with both researchers and businessmen seeking new, innovative and effective methods. These methods usually involve large numbers of participants who are drawn from within the client and developer organisations. This is a financially costly characteristic of the requirements elicitation process. Besides information systems, the technology revolution has also brought sophisticated communication technologies into the marketplace. These communication technologies allow people to communicate with one another in a variety of different time and space scenarios. An important spin-off of this is the ability for people located in significantly different geographical locations to work collaboratively on a project. It is claimed that this approach to work has significant cost and productivity advantages. This study draws the requirements elicitation process into the realm of collaborative work. Important project management, communication, and collaborative working principles are examined in detail, and a model is developed which represents these issues as they pertain to the requirements elicitation process. An empirical study (conducted in South Africa) is performed in order to examine the principles of the model and the relationships between its constituent elements. A model of geographically distributed requirements elicitation (GDRE) is developed on the basis of the findings of this investigation. The model of GDRE is presented as a 3-phased approach to requirements elicitation, namely planning, implementation, and termination. Significantly, the model suggests the use of interviews, structured workshops, and prototyping as the chief requirements elicitation methods to be adopted in appropriate conditions. Although a detailed study of communications technology was not performed, this thesis suggests that each individual GDRE implementation requires a different mix of communication technologies to support its implementation.
Keywords: Management information systems -- Management; Information resources management; System design; System analysis